Treatment with Non-specific HDAC Inhibitors Administered after Disease Onset does not Delay Evolution in a Mouse Model of Progressive Multiple Sclerosis. (15th June 2021) - Buonvicino, Daniela; Ranieri, Giuseppe; Chiarugi, Alberto
Graphical abstract: Highlights: HDACi post onset-treatment does not delay disease evolution during progressive EAE. This occurs in spite of evidence of suppression of autoreactive lymphocytes. Progression of EAE becomes independent from autoimmunity at symptom onset. PMS therapy with HDACi needs to be reevaluated. Abstract: Drugs able to efficiently counteract progression of multiple sclerosis (MS) are still an unmet need. Several lines of evidence indicate that histone deacetylase inhibitors (HDACi) are clinically-available epigenetic drugs that might be repurposed for immunosuppression in MS therapy. Here, we studied the effects of HDACi on disease evolution in myelin oligodendrocyte glycoprotein (MOG)-immunized NOD mice, an experimental model of progressive experimental autoimmune encephalomyelitis (PEAE). To obtain data of potential clinical relevance, the HDACi panobinostat, givinostat and entinostat were administered orally adopting a daily treatment protocol after disease onset. We report that the 3 drugs efficiently reduced in vitro lymphocyte proliferation in a dose-dependent manner. Notably, however, none of the drugs delayed evolution of PEAE or reduced lethality in NOD mice. In striking contrast with this, however, the lymphocyte proliferation response to MOG as well as Th1 and Th17 spinal cord infiltrates were significantly lower in animals exposed to the HDACi compared to those receiving vehicle. When put into a clinical context, for the first time data cast doubt on the relevance of HDACi to treatment of progressive MS (PMS). Also, our findings further indicate that, akin to PMS, neuropathogensis of PEAE in NOD mice becomes independent from autoimmunity, thereby corroborating the relevance of this model to experimental PMS research.